2022
DOI: 10.3389/fpsyt.2022.840120
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variants Associated With Resilience in Human and Animal Studies

Abstract: Resilience is broadly defined as the ability to maintain or regain functioning in the face of adversity and is influenced by both environmental and genetic factors. The identification of specific genetic factors and their biological pathways underpinning resilient functioning can help in the identification of common key factors, but heterogeneities in the operationalisation of resilience have hampered advances. We conducted a systematic review of genetic variants associated with resilience to enable the identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 321 publications
0
3
0
1
Order By: Relevance
“…Genetic and epigenetic factors are major contributors to vulnerability or resilience to stress ( Ising and Holsboer, 2006 ; Cahill et al, 2022 ). For example, recent studies identified a major role for the glial-derived neurotrophic factor (GDNF) in response to chronic unpredictable stress (CUS): Increased GDNF expression in nucleus accumbens and hippocampus promotes resilience and recovery from CUS ( Uchida et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic and epigenetic factors are major contributors to vulnerability or resilience to stress ( Ising and Holsboer, 2006 ; Cahill et al, 2022 ). For example, recent studies identified a major role for the glial-derived neurotrophic factor (GDNF) in response to chronic unpredictable stress (CUS): Increased GDNF expression in nucleus accumbens and hippocampus promotes resilience and recovery from CUS ( Uchida et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, knowledge of potential mediators of the relationship between CM and resilience, e.g. (epi)genetic factors (Cahill et al, 2022 ; Choi et al, 2019 ; Cicchetti & Rogosch, 2012 ; Gallardo-Pujol et al, 2013 ; Goldberg et al, 2013 ; Miu et al, 2017 ; Ramo-Fernández et al, 2019 ), brain structure (Roeckner et al, 2021 ) and functioning (McCrory et al, 2017 ; Ohashi et al, 2017 ; Teicher et al, 2020 ; Teicher & Samson, 2016 ), past or current mental disorder or medical condition (Ashy et al, 2020 ; Perini et al, 2023 ), personality traits (Mrazek & Mrazek, 1987 ), (insecure) attachment styles (Citak & Erten, 2021 ; Stein, 2006 ), physical activity or exercise (Arida & Teixeira-Machado, 2020 ), perceived loneliness, social network size and services, and coping strategies (Reinhard et al, 2022 ; Su et al, 2022 ; Ungar, 2013 ) could facilitate an understanding of the mechanisms underlying this association. This knowledge is important for developing risk stratification models of adverse psychosocial health outcomes and targeted effective prevention and intervention strategies for individuals with histories of CM exposure.…”
Section: Introductionmentioning
confidence: 99%
“…APOE (apolipoprotein, apoE) encodes a major apoprotein of the chylomicron family. It has been suggested that APOE, along with FKBP5, OXTR, and CRHR1, is among the main genes associated with resilience across divergent resilience definitions [62]. Stress induces apoE synthesis as part of repair processes in the central nervous system [63].…”
Section: Introductionmentioning
confidence: 99%